Child-Friendly School Environment: A Case of Community Schools of Pokhara - Tripathi, Krishna Prasad (Prithvi Journal of Research and Innovation, 2020)
The study is carried out to investigate the status of child-friendly school environment, and identify school’s policy towards it. It was delimited to Pokhara Metropolitan of Kaski District. To accomplish the objectives, the explanatory sequential research design was used. The survey technique was used for quantitative and observation was used to qualitative study. There were 128 basic community schools. Eleven schools were selected randomly. The interview schedule and observation checklist were the major tools of data collection. Collected data and information were analyzed both quantitatively as well as qualitatively as per their nature in the table. The findings of the study demonstrated that physical facilities in community schools in Pokhara Metropolitan City seem satisfactory. The researcher asked and observed the school sites. More than one quarter schools (27.3%) had peace and quiet place to teach. More than one-third school (36.4%) had satisfactory and the same (36.4%) had no open and enough space. The study also found that all schools had little raised and dry land and not to risk of sinking during the monsoon. More than half of the schools (54.5%) had the satisfactory situation on sufficient space and on adequate water and facility of waste disposal. From the observation, it was found that nearly two third schools had poor situation of restrooms without water and latches. It is concluded that the community schools tried their best to make child-friendly school environment, but those attempts were found to be insufficient. The study recommended that communication, cooperation, and coordination are needed among the stakeholders to plan for the quality education in schools.